Electrochemical characterization of Graphene-based transducers for biosensor development - Arris, Farrah Aida; Wan Salim, Wan Wardatul Amani (IIUM, 2016)
Electrochemical characterization of graphene-based nanocomposites as transducer material for highly sensitive biosensors was performed. Parameters that were varied include graphene oxide (GO) concentration and amount of added gold nanoparticles (AuNPs) as well as Nafion as binder for enhancing electrical conductivity of the transducer layer. The nanocomposite-modified GCE transducer layers were fabricated via a simple two-step drop-cast and subsequent electrochemical reduction. Cyclic voltammetry (CV) was used to characterize the redox capability of the transducer layer. Electrochemical deposition of ultra-highly-concentrated single-layer graphene oxide (UHC GO) suspension with a concentration of 6.2 mg/ml gave higher anodic peak current, Ipa, after electrochemical reduction compared to most peak currents reported in the literature for a 3-mm inner-diameter electrode; adding UHC GO:AuNPs in a 2:1 ratio followed by electrochemical reduction resulted in even higher Ipa, whereas adding UHC GO:Nafion in a 4:1 ratio gave promising results for prolonged shelf-life of the biosensor. Therefore, UHC GO-AuNPs-Nafion as nanocomposite is an excellent precursor for the development of a redox-active transducer that results in highly sensitive biosensors.